Association between prognosis and the use of angiotensin‐converting enzyme inhibitors and/or angiotensin II receptor blockers in frail patients with heart failure with preserved ejection fraction. (24th March 2022) - Sunaga, Akihiro; Hikoso, Shungo; Tamaki, Shunsuke; Seo, Masahiro; Yano, Masamichi; Hayashi, Takaharu; Nakagawa, Akito; Nakagawa, Yusuke; Kurakami, Hiroyuki; Yamada, Tomomi; Kitamura, Tetsuhisa; Sato, Taiki; et al.
Abstract: Aims: The effectiveness of angiotensin‐converting enzyme inhibitors (ACE‐I) and angiotensin II receptor blockers (ARB) has not been demonstrated in patients with heart failure with preserved ejection fraction (HFpEF). We recently reported significant interaction between the use of ACE‐I and/or ARB (ACE‐I/ARB) and frailty on prognosis in patients with HFpEF. In the present study, we examined the association between ACE‐I/ARB and prognosis in patients with HFpEF stratified by the presence or absence of frailty. Methods and results: We examined the association between the use of ACE‐I/ARB and prognosis according to the presence [Clinical Frailty Scale (CFS) ≥ 5] or absence (CFS ≤ 4) of frailty in patients with HFpEF in a post hoc analysis of registry data. Primary endpoint was the composite of all‐cause mortality and heart failure admission. Secondary endpoints were all‐cause mortality and heart failure admission. Of 1059 patients, median age was 83 years and 45% were male. Kaplan–Meier analysis showed that the risk of composite endpoint (log‐rank P = 0.001) and all‐cause death (log‐rank P = 0.005) in patients with ACE‐I/ARB was lower in those with CFS ≥ 5, but similar between patients with and without ACE‐I/ARB in patients with CFS ≤ 4 (composite endpoint: log‐rank P = 0.830; all‐cause death: log‐rank P = 0.192). In a multivariable Cox proportional hazards model, use of ACE‐I/ARB was significantly associated with lower risk of the composite endpoint [hazard ratio (HR) = 0.52, 95% confidence interval (CI) = 0.33–0.83, P = 0.005] and heart failure admission (HR = 0.45, 95% CI = 0.25–0.83, P = 0.010) in patients with CFS ≥ 5, but not in patients with CFS ≤ 4 (composite endpoint: HR = 1.41, 95% CI = 0.99–2.02, P = 0.059; heart failure admission: HR = 1.43, 95% CI = 0.94–2.18, P = 0.091). The association between ACE‐I or ARB and prognosis did not significantly differ by CFS (CFS ≤ 4: log‐rank P = 0.562; CFS ≥ 5: log‐rank P = 0.100, for with ACE‐I vs. ARB, respectively). Adjusted HRs for CFS 1–4 were higher than 1.0 but were <1.0 at CFS 5. Conclusions: In patients with HFpEF, use of ACE‐I/ARB was associated with better prognosis in patients with frailty as assessed with the CFS, but not in those without frailty.